Large-scale association analyses identify host factors influencing human gut microbiome composition - Kurilshikov, Alexander; Medina-Gomez, Carolina; Bacigalupe, Rodrigo; Radjabzadeh, Djawad; Wang, Jun; Demirkan, Ayse; Le Roy, Caroline I.; Raygoza Garay, Juan Antonio; Finnicum, Casey T.; Liu, Xingrong; Zhernakova, Daria V.; Bonder, Marc Jan; et al. (Nature genetics, 2021)
To study the effect of host genetics on gut microbiome composition, the MiBioGen consortium curated and analyzed genome-wide genotypes and 16S fecal microbiome data from 18,340 individuals (24 cohorts). Microbial composition showed high variability across cohorts: only 9 of 410 genera were detected in more than 95% of samples. A genome-wide association study of host genetic variation regarding microbial taxa identified 31 loci affecting the microbiome at a genome-wide significant ( P < 5 × 10 −8 ) threshold. One locus, the lactase ( LCT ) gene locus, reached study-wide significance (genome-wide association study signal: P = 1.28 × 10 −20 ), and it showed an age-dependent association with Bifidobacterium abundance. Other associations were suggestive (1.95 × 10 −10 < P < 5 × 10 −8 ) but enriched for taxa showing high heritability and for genes expressed in the intestine and brain. A phenome-wide association study and Mendelian randomization identified enrichment of microbiome trait loci in the metabolic, nutrition and environment domains and suggested the microbiome might have causal effects in ulcerative colitis and rheumatoid arthritis. Analysis of human genotypes and 16S microbiome data of 18,473 individuals from 25 cohorts through a genome-wide association study, a phenome-wide association study and Mendelian randomization identifies host genetic and microbial trait associations.